2015
DOI: 10.1111/mec.13231
|View full text |Cite
|
Sign up to set email alerts
|

Migration‐related phenotypic divergence is associated with epigenetic modifications in rainbow trout

Abstract: Migration is essential for the reproduction and survival of many animals, yet little is understood about its underlying molecular mechanisms. We used the salmonid Oncorhynchus mykiss to gain mechanistic insight into smoltification, which is a morphological, physiological, and behavioral transition undertaken by juveniles in preparation for seaward migration. O. mykiss is experimentally tractable and displays intra- and inter-population variation in migration propensity. Migratory individuals can produce non-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 121 publications
5
119
0
Order By: Relevance
“…One good example of the power of epigenetics in QTL mapping is Cortijo et al (2014), which recently reported several methylated regions that acted as QTLs and accounted for 60-90% of the heritable variation for flowering time and primary root length in Arabidopsis. The important role that epigenetics can play in fish has been highlighted by Baerwald et al (2016), who identified differential methylation patterns between rainbow trout individuals with different migratory behaviour. To facilitate the future use of epigenetics in research, high-throughput sequencing technology can be used to detected both DNA sequence variation and certain epigenetic markers and modifications (e.g.…”
Section: Epigenetic Markersmentioning
confidence: 99%
“…One good example of the power of epigenetics in QTL mapping is Cortijo et al (2014), which recently reported several methylated regions that acted as QTLs and accounted for 60-90% of the heritable variation for flowering time and primary root length in Arabidopsis. The important role that epigenetics can play in fish has been highlighted by Baerwald et al (2016), who identified differential methylation patterns between rainbow trout individuals with different migratory behaviour. To facilitate the future use of epigenetics in research, high-throughput sequencing technology can be used to detected both DNA sequence variation and certain epigenetic markers and modifications (e.g.…”
Section: Epigenetic Markersmentioning
confidence: 99%
“…As a result of these advances, epigenetics studies in aquaculture have tremendously increased in the last decades with the view to identifying biological markers relevant for improving the production of farmed aquatic organisms. Technologies used for epigenetics analyses in aquaculture include (i) RNA-seq in Medaka [207] and Nile tilapia [208]; (ii) genome-wide methylated DNA immunoprecipitation sequencing (MeDIP-seq) in Nile tilapia [209] and Medaka [207]; (iii) bisulite sequencing (BS-seq) in smooth tongue sole (Cynoglossus semilaevis) [210,211], rainbow trout [212] and Nile tilapia [208]; (iv) genetic linkage map analysis using simple sequence length polymorphisms (SSLPs) in medaka [213,214]; (v) methylation sensitivity ampliied polymorphism (MSAP) in Atlantic salmon [18], grass carp [215], brown trout [17], sea urchin (Glyptocidaris crenularis) [216] and sea cucumber (Apostichopus japonicas) [217]; (vi) 5-methylcytosine immunolocation in sea lamprey (Petromyzon marinus) [218]; (vii) restriction endonuclease hydrolysis of DNA using methylation enzymes in Zebraish [219] and (viii) bisulite sequencing PCR in Paciic Oyster (Crassostrea gigas) [220] and grass carp [221]. As shown in Table 3, epigenetics studies carried out this far include studies on reproduction, growth and adaptation traits.…”
Section: Application Of Epigenetics In Aquaculturementioning
confidence: 99%
“…Control of gonadal aromatase [263] Daphnia magna Male meiosis [227] Paciic oyster (Crassostrea gigas) Growth [220] Rainbow trout (Oncorhynchus mykiss) Glucose intolerance [230] Rainbow trout (Oncorhynchus mykiss) Migration-related phenotypic divergence [212] Atlantic Cod (Gadus morhua L.) Photoperiod inluence [228,229] Grass carp (Ctenopharyngodon idella) Individual variations [215] Grass carp (Ctenopharyngodon idella) Resistance against grass reovirus [221] parr and mature ish. However, epigenetic analysis showed signiicant single-locus variations in the gonads followed by the brain and liver between parr and mature ish suggesting that early maturation in Atlantic salmon parr was mediated by epigenetic processes and not genetic diferences.…”
Section: Scripta Elegans)mentioning
confidence: 99%
See 1 more Smart Citation
“…, DNA methylation and histone modifications) on gene expression (de la Paz Sanchez et al 2015). Furthermore, epigenetic mechanisms are involved in phenotypic plasticity (Slepecky and Starmer 2009; Bossdorf et al 2010; Herrera et al 2012; Baerwald et al 2016) and transgenerational inheritance (Verhoeven et al 2010; Verhoeven and van Gurp 2012; Luna and Ton 2012; Rasmann et al 2012; Ou et al 2012; Öst et al 2014; Siklenka et al 2015). While experiments that have artificially induced variation in DNA methylation have shown how this factor can contribute significantly to phenotypic variation (Cortijo et al 2014) and plasticity (Kooke et al 2015), the relative importance of other epigenetic modifications—even the extent to which their effects are environmentally dependent—remains unclear.…”
mentioning
confidence: 99%